Pinguicula zamudioana (Lentibulariaceae) a new species endemic to western Mexico - Juárez-Gutiérrez, Héctor David; Muñiz-Castro, Miguel Ángel; Hernández-Rendón, Julián; Nuño-Rubio, Ana Teresa (Phytotaxa, 2018)
Pinguicula zamudioana (Lentibulariaceae), a new species endemic to western Mexico, is described and illustrated. This new species belongs to Pinguicula section Orcheosanthus and is morphologically close to Pinguicula oblongiloba and P. michoacana, but differs in having a homophyllous rosette with a single type of leaves (summer leaves), light green leaves with glabrous petioles, short peduncles, a calyx with triangular-lanceolate to lanceolate lobes, a pink corolla with oblong to suborbiculate lobes and the fact that it only inhabits calcium concretions. Pinguicula zamudioana is easily distinguished from the other two taxa, due to the lack of a winter rosette, i.e. isomorphic leaves during the entire year, and to the fact that it is in constant growth and blooms all year round.